Metathesis in the Production of Written Texts in Quechua - Calsín Vilca, David Peter (2021)
Language and linguistic normalization are constant concerns for intellectuals who are dedicated to teaching Andean languages. Quechua is not exempt from this need, since it still laks a standard writing system and fragmented into several dialects. Iit requires studies that contribute to its standardization. For this reason, we focus our interest in determining the realization morphological context of the root alternation metathesis in the production of written texts in Quechua by students of UNSCH, 2013.